2000
DOI: 10.1148/radiology.216.2.r00au10586
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Measurement of Phalanges: Comparison of Radiographic Absorptiometry and Area Dual X-ray Absorptiometry

Abstract: With a standard, image-intensifier-based, digital radiographic system, high-spatial-resolution images of the hand were acquired for analysis of phalangeal bone mineral density with dual x-ray absorptiometry (DXA). Results with phalangeal DXA had precision of plus or minus 0.67% and accuracy of 4.1% and correlated well with those with radiographic absorptiometry. This phalangeal DXA technique is potentially useful for clinical diagnosis of osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 36 publications
1
23
0
3
Order By: Relevance
“…Scans were analysed as described previously [40]. Briefly, a calibrating phantom composed of air, water and cortical bonemimicking epoxy (SB3; Gammex, Middleton WI, USA) [41] was scanned together with the animals. On the eXplore Locus Ultra, 1,000 projection images were obtained over a single 16- .…”
Section: Micro-computed Tomography (Micro-ct)mentioning
confidence: 99%
“…Scans were analysed as described previously [40]. Briefly, a calibrating phantom composed of air, water and cortical bonemimicking epoxy (SB3; Gammex, Middleton WI, USA) [41] was scanned together with the animals. On the eXplore Locus Ultra, 1,000 projection images were obtained over a single 16- .…”
Section: Micro-computed Tomography (Micro-ct)mentioning
confidence: 99%
“…[16] This can account for the differences between this study and that of Shiarishi et al [17] This loss of calcium is, nevertheless, important, as hypercalciuria is one of the most common features of postmenopausal bone loss with osteoporosis in 50% of patients. [18,19] As the name refers, bone mineral density is a measure of the mineral content of a bone or specific region of a bone and, therefore, it indicates a measure of strength of a bone. In the present study, the diameters of the tibial head and shaft were significantly reduced in the unsupplemented Ovx group.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been also reported in the literature. [9,[19][20][21] A reduction in the bone mineral density has been reported for the greater trochanter, shaft, and distal epiphysis of the femur in the Ovx rats, compared to the Shm group. [16] In addition, Giavaresi et al [22] reported that, in rats treated with alendronate sodium following ovariectomy, there was a 15% increase in the bone density in the femoral epiphysis, compared to the control group, and a 27% increase, compared to the Ovx unsupplemented group.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of this technique in its original form was about 6%, with an in-vivo, inter-radiograph precision error of about 2% (Colbert and Bachtell 1981). The application of dualenergy principles, special film and automatic or semi-automatic computer analysis improved the accuracy of the technique to 4.1% (Gulam et al 2000). No comparative data for current in-vivo, inter-radiograph precision were found.…”
Section: Radiographic Absorptiometrymentioning
confidence: 99%